Acute inhalation toxicity of smoke of fentanyl and its 1-substituted analogs in Swiss albino mice - Yadav, S. K.; Swami, D.; Kumar, P.; Meena, M. K.; Maurya, C. K.; Gupta, P. K.; Ganesan, K.; Jain, A. K.; Bhattacharya, R. (Cellular and Molecular Biology, 2014)
Fentanyl (N-(1-phenethyl-4-piperidinyl)propionanilide) is a synthetic, potent narcotic analgesic agent. However, it is known to have several side effects, which led to synthesis and evaluation of its new analogs for the management of pain. We have earlier reported the comparative bioassay of fentanyl and its eight 1-substituted analogs (1-8) in mice. Three compounds, viz., N-(1-(2-phenoxyethyl)-4-piperidinyl)propionanilide (2), N-isopropyl-3-(4-(N-phenylpropionamido)piperidin-1-yl)propanamide (5), and N-t-butyl-3-(4-(N-phenylpropionamido)piperidin-1-yl)propanamide (6) were found to be more effective and less toxic compared to fentanyl. The present study reports the comparative acute inhalation toxicity of smoke of fentanyl and its three analogs, viz., 2, 5, and 6 in mice. Animals were exposed to different concentrations of smoke generated by heating the compounds. Exposure was performed in a head only all glass static exposure assembly for 15 min to determine the median lethal concentration (LC50). The breathing pattern and various respiratory parameters of the animals were also monitored online using a polygraph. Out of three compounds tested, analog 5 was found to be most toxic (LC50 = 2820 mg/m3) while 2 was least toxic (LC50 = >8000 mg/m3). All the compounds caused long lasting respiratory depression in a dose- dependent manner, which did not completely resolve even after discontinuation of exposure. Aerodynamic median diameter and geometric standard deviation of smoke particles was determined employing eight-stage Andersen sampler. The particles were found to be within the respirable range. The study, however, concludes that due to possible decomposition of the compounds by heating or its poor absorption by the alveolar surface, the present inhalation technique cannot be employed to generate smoke of fentanyl and its analogs for any medical or surreptitious use.